1986
DOI: 10.1007/bf01869017
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Cl− transport across the mucosal and serosal membranes of urodele intestinal cells

Abstract: The characteristics of Cl- movement across luminal and basolateral membranes of Amphiuma intestinal absorptive cells were studied using Cl(-)-sensitive microelectrodes and tracer 36Cl techniques. Intracellular Cl- activity (aiCl) was unchanged when serosal Cl- was replaced; when luminal Cl- was replaced cell Cl- was rapidly lost. Accordingly, the steady state aiCl could be varied by changing the luminal [Cl]. As luminal [Cl] was raised from 1 to 86 mM, aiCl rose in a linear manner, the mucosal membrane hyperpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The finding that the efflux of Cl-from Necturus enterocytes is dominated by movements across the apical membrane is analogous to that of White (1986) for -Amphiuma small intestine and that-of Zuidem'ab et al (1985) for goldfish intestinal epithelium. The effects of mucosal Cl-replacement on Em in the goldfish are also consistent with the presence of an apical Cl-conductance, although this is not 'thtconclusion reached by the authors.…”
Section: Comparison With Other Epithelial Tissuessupporting
confidence: 50%
See 1 more Smart Citation
“…The finding that the efflux of Cl-from Necturus enterocytes is dominated by movements across the apical membrane is analogous to that of White (1986) for -Amphiuma small intestine and that-of Zuidem'ab et al (1985) for goldfish intestinal epithelium. The effects of mucosal Cl-replacement on Em in the goldfish are also consistent with the presence of an apical Cl-conductance, although this is not 'thtconclusion reached by the authors.…”
Section: Comparison With Other Epithelial Tissuessupporting
confidence: 50%
“…(Lew, Ferreira & Moura, 1979 (White, 1986; F. Giraldez, F. V. Sepuilveda & D. N. Sheppard, unpublished observations) and the intracellular concentration of Na+ is also very low (our measurements with double-barrelled Na+-selective microelectrodes gave values of 10-6 + 3-8 mm for nine cells with Em = -33-3 + 6-3 mV), eqn (1) can be further simplified for symmetrical concentrations of K+ and 601 F. GIRALDEZ, F. V. SEPULVEDA AND D. N. SHEPPARD Na+ ions in the bathing solutions. In this case the change in cell potential after bathing the mucosal membrane with a low-Cl-solution will be given by: …”
Section: Electrical Arrangementsmentioning
confidence: 99%
“…A Na-HC03/Cl transport system was first described in the snail neuron (Thomas, 1977), barnacle muscle (Boron et al, 1981), and squid giant axon (Boron & Russell, 1983) and subsequently characterized in the Amphiuma intestinal mucosa (White, 1986) and in cultured bovine corneal endothelium (Jentsch et al, 1985). With the use of Cl and pH-sensitive microelectrodes, this transporter was described in the basolateral membrane of Necturus proximal tubule ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the basolateral exit step for anions has not been clearly determined. Recent studies have suggested several possible anion transport mechanisms, many of which are sensitive to stilbenes and furosemide (15)(16)(17)(18)(19)(20). The basolateral membrane quite clearly has a multiplicity of possible transport systems; further studies will be required to resolve the complexity of these systems.…”
Section: Discussionmentioning
confidence: 99%